Association Between Respiratory Alkalosis and the Prognosis of COVID-19 Patients - Wu, Chenfang; Wang, Guyi; Zhang, Quan; Yu, Bo; Lv, Jianlei; Zhang, Siye; Wu, Guobao; Wu, Shangjie; Zhong, Yanjun (Frontiers in Medicine, 2021)
Aim: The aim of the study was to describe the clinical characteristics of patients with or without respiratory alkalosis, and analyze the relationship of respiratory alkalosis and the outcome of adult coronavirus disease 2019 (COVID-19) patients. Methods: Clinical and laboratory data of adult COVID-19 patients in a single center in China, were retrospectively collected and analyzed. The Kaplan-Meier (KM) curve and cox regression were adopted to analyze the association between respiratory alkalosis and prognosis of COVID-19 patients. Results: Of 230 adult COVID-19 patients, 66 patients (28.7%) had respiratory alkalosis on admission. Of 66 patients, the median age was 53 years old (range, 21-84 years), and 43 (65.2%) were female. Compared with those without respiratory alkalosis, patients with respiratory alkalosis were significantly older (P = 0.002), had a higher proportion of female (P = 0.004), and showed higher ratios of underlying diseases including hypertension (P = 0.023) and cardiovascular disease (P = 0.028). Moreover, they demonstrated higher proportion of severe events (P = 0.001). Patients with respiratory alkalosis had a higher possibility of developing severe events compared with those without respiratory alkalosis (Log Rank P = 0.001). After adjusting for gender, age, and comorbidities, patients with respiratory alkalosis still showed significantly elevated risks of developing to severe cases (HR 2.445, 95% CI 1.307-4.571, P = 0.005) using cox regression analyses. Conclusions: Respiratory alkalosis as a common acid - base disorder in COVID-19 patients, was associated with a higher risk of developing severe event.